Uzupełnij.
a) 6x-(y = .....(2x-3y)
b) 4xy-6x = .... (2y-3)
c) 12p²q - 2pq = ......(6p-1)
d) -9a²-6ab= -3a (........)
e) p- ½r=½ (.........)
f) 4x-y =4 (.......)
g) a-3b = 3 (........)
h) 5x+5y+1= 5 (......)
i) 6cd² -cd =2cd (....)
j) a²b-2a³ =½a²(.....)

Proszę o pomoc,bo wogóle nic nie rozumiem z matematyki. Z góry dzięki ;)

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T16:24:06+01:00
A) 6x-(y = .x-y....(2x-3y)
b) 4xy-6x = xy-x.... (2y-3)
c) 12p²q - 2pq = ..p-k....(6p-1)
d) -9a²-6ab= -3a (...5x.....)
e) p- ½r=½ (6a...)
f) 4x-y =4 (.....7b.)
g) a-3b = 3 (....4....)
h) 5x+5y+1= 5 (...x...)
i) 6cd² -cd =2cd (.b...)
j) a²b-2a³ =½a²(....a.)
1 3 1
2010-03-12T16:35:27+01:00
A) 6x-y = x-y (2x-3y)
b)4xy-6x = xy-x (2y-3)
c) 12p²q - 2pq = p-k (6p-1)
d) -9a²-6ab= -3a (5x)
e) p- ½r=½ (6a)
f) 4x-y =4 (7b)
g) a-3b = 3 (4)
h) 5x+5y+1= 5 (x)
i) 6cd² -cd =2cd (b)
j) a²b-2a³ =½a²(a)


Mam nadzieje, że pomogłam
Pozdrawiam!!!
2010-03-12T16:52:27+01:00
A) 6x - y = x - y (2x-3y)
b) 4xy - 6x = xy - x (2y-3)
c) 12p²q - 2pq = p - k (6p-1)
d) -9a² - 6ab = -3a (3a + 2b)
e) p- ½r = ½ (2p - r)
f) 4x - y = 4 (x - ¼y)
g) a - 3b = 3 (⅓a - b)
h) 5x + 5y + 1 = 5 (x + y + ⅕)
i) 6cd² - cd = 2cd (3b - ½)
j) a²b - 2a³ = ½a²(2b - 4a)

Chyba jest dobrze.